Basement Characteristics of Jakarta Groundwater Basin Based on Satellite Gravimetry Data - Gumilar Utamas Nugraha; Lina Handayani; Rachmat Fajar Lubis; Dadan Dani Wardhana; Karit Lumban Gaol (Faculty of Geography, Universitas Gadjah Mada, 2020)
Jakarta groundwater basin is one of the most developed basins in Indonesia as Jakarta city is located within the basin, with an elevation ranging from 0 to 1000 m above sea level. The study of the basement characteristics of groundwater basins still needs further study in the Jakarta Groundwater Basin. The objective of this study is to examine the basement characteristics of Jakarta Groundwater Basin by satellite gravimetry. Gravity forward models were constructed using Oasis Montaj and 2-D GM-SYS software for two north-south sections, A and B, and west-east section C-D. Regional anomalies in the study area with a value range of 36.7 to 53.2 mGal, while the residual anomaly values in the study area were in the range of -7.0 - 10.0 mGal. There are four rock formations based on forwarding modeling. Holocene Beach Ridge Deposit formation has a density of 2.0 gr/cc. The thickness of this formation is estimated to be around 10-20 meters. Late Pleistocene Alluvial fan has a density of about 2.2 gr/cc. The depth of this layer ranges from 10-50 meters. Early Pleistocene Formation, has a density of 2.35 gr/cc. The thickness of this formation is at a depth of 50-200 meters in the cross-section. The Tertiary Marine Sediment Formation is a basement of the Jakarta Groundwater Basin. This formation has a rock density of 2.45 gr/cc.